Bioecologia do parasitoide Cleruchoides noackae (Hymenoptera: Mymaridae) em ovos de Thaumastocoris peregrinus (Hemiptera: Thaumastocoridae) - Becchi, Luciane Katarine [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The bronze bug Thaumastocoris peregrinus Carpintero & Dellapé, 2006 (Hemiptera: Thaumastocoridae) is an eucalypt sap-sucking, native of Australia, present in Brazil since 2008. Its distribution and dissemination, in aggregate form, was fast in the producing states of eucalyptus, being reported causing damages in plantations in 14 states Brazilians. In 2012, the parasitoid of eggs Cleruchoides noackae Lin & Huber, 2007 (Hymenoptera: Mymaridae) was introduced in the country for laboratory mass-rearing and release into the field for the biological control of the population of the bronze bug. However, there are few studies on a C. noackae biology and behavior and dynamics between the parasitoid and its host. The objective was to determine the thermal requirements and the duration of C. noackae development in eggs of T. peregrinus at different temperatures; to evaluate the parasitism of C. noackae in T. peregrinus eggs at different temperatures and to study, under laboratory conditions, the parasitoid courtship, mating and oviposition behaviour and the parasitism of virgin and mated females of C. noackae on T. peregrinus eggs. The temperature, influenced the development time of C. noackae, observing reduction of the biological cycle (egg-adult) with the increase of the temperature. Females and males of the parasitoid require temperatures above 7.34°C and 7.59°C and accumulation of 298.50 and 289.85 degrees day, respectively, for their development. The viability of emergence was affected by temperature with 20% of parasitoids retained (not emerged) at 30ºC. The temperature also influenced the parasitism of C. noackae in T. peregrinus eggs. Temperatures ranging from 21 to 27ºC were better for the parasitism of C. noackae in eggs of T. peregrinus with the highest rate of parasitism occurs within the first 24h. In the behavioral study of C. noackae, no courtship behavior was observed and only one copula between the couple occurred. Virgins and copulated females found the first host in 15.21 and 17.14 minutes and the next host in 3.85 and 0.86 minutes, respectively. The foraging time and duration of ovipositor insertion into T. peregrinus eggs was 24 and 21 seconds and 5.13 and 3.69 minutes, respectively. Virgins and copulated females of C. noackae inserted the ovipositor more frequently on the sides of the egg and operculum of the T. peregrinus egg. At one hour, more than 50% of T. peregrinus eggs offered to C. noackae females were parasitized, indicating high and rapid parasitism. The sex ratio of 0.00 (virgin females) and 0.68 (females copulated) confirming the arrhenotokous parthenogenesis of C. noackae. Female virgins and copulated C. noackae have similar parasitism capacity in the laboratory, 89%, however, the viability of emergence is lower for copulated females. The results presented in this work can be used for adjustment of techniques for parasitoid mass-rearing and bronze bug management.

O percevejo-bronzeado, Thaumastocoris peregrinus Carpintero & Dellapé, 2006 (Hemiptera: Thaumastocoridae), nativo da Austrália, está presente no Brasil desde 2008. De forma agregada, a distribuição e disseminação do percevejo-bronzeado foi rápida nos estados produtores de eucalipto, sendo relatado causando danos em plantios em 14 estados brasileiros. Em 2012, o parasitoide de ovos Cleruchoides noackae Lin & Huber, 2007 (Hymenoptera: Mymaridae) foi introduzido no país, para criação massal em laboratório e liberação à campo, para o controle biológico da população do percevejo-bronzeado. No entanto, ainda há poucos estudos de biologia e comportamento de C. noackae e da dinâmica entre o parasitoide e o hospedeiro. O objetivo foi determinar as exigências térmicas e duração do desenvolvimento de C. noackae, em ovos de T. peregrinus, em diferentes temperaturas; avaliar o parasitismo de ovos de T. peregrinus, por C. noackae em diferentes temperaturas, e estudar, em condições de laboratório, o comportamento de corte, acasalamento e oviposição e o parasitismo de fêmeas virgens e acasaladas de C. noackae em ovos de T. peregrinus. A temperatura, influenciou o tempo de desenvolvimento de C. noackae, notando-se redução do período ovo-adulto com o aumento da temperatura. Fêmeas e machos do parasitoide necessitam de temperaturas acima de 7,34°C e 7,59°C e acúmulo de 298,50 e 289,85 graus-dia, respectivamente, para completar o desenvolvimento. A viabilidade de emergência foi também, afetada pela temperatura, com 20% de parasitoides retidos (não emergidos) a 30ºC. A temperatura influenciou, o parasitismo de C. noackae em ovos de T. peregrinus. Temperaturas entre 21 e 27ºC foram as melhores para o parasitismo de C. noackae em ovos de T. peregrinus, com maior taxa de parasitismo nas primeiras 24 horas. No estudo comportamental de C. noackae, não foi observado comportamento de côrte e ocorre apenas uma cópula entre o casal. Fêmeas virgens e copuladas encontraram o primeiro hospedeiro em 15,21 e 17,14 minutos e os demais em 3,85 e 0,86 minutos, respectivamente. O tempo de forrageamento e inserção do ovipositor de fêmeas virgens e copuladas C. noackae em ovos de T. peregrinus, foi de 24 e 21 segundos e de 5,13 e 3,69 minutos, respectivamente. Fêmeas virgens e copuladas inseriram o ovipositor com maior frequência nas laterais e opérculo do ovo de T. peregrinus. Em uma hora, mais de 50% dos ovos de T. peregrinus oferecidos às fêmeas de C. noackae foram parasitados, indicando alto e rápido parasitismo. A razão sexual de 0,00 (fêmeas virgens) e 0,68 (fêmeas copuladas) confirmam a partenogênse arrenótoca de C. noackae. Fêmeas virgens e copuladas de C. noackae tem capacidade semelhante de parasitismo em laboratório, 89%, porém, a viabilidade de emergência do parasitoide é menor para fêmeas copuladas. Os resultados apresentados neste trabalho podem ser utilizados para o ajuste de técnicas de criação massal em laboratório deste parasitoide e manejo do percevejo-bronzeado.
Bioecology of parasitoide Cleruchoides noackae (Hymenoptera: Mymaridae) in eggs of Thaumastocoris peregrinus (Hemiptera: Thaumastocoridae)
Keywords: Behaviour; Biology; Bronze bug; Egg parasitoid; Biologia; Comportamento; Eucalyptus; Parasitoide de ovos; Percevejo-bronzeado